# Prove that $\sum\limits_{i=1}^n 2i\binom{2n}{n-i}= n\binom{2n}{n}$

Let n be a positive integer.

Prove that $$\sum_{i=1}^n 2i\binom{2n}{n-i}= n\binom{2n}{n}$$

• And... what did you try? – Did Mar 23 '13 at 13:56
• Have you tried reversing your summation order and see if you recognize anything? – J. M. is a poor mathematician Mar 23 '13 at 13:56

## 2 Answers

Here’s an alternative that requires a little less of a leap to get started, but a little more algebra later. Instead of pulling $2i=(n+i)-(n-i)$ out of thin air, substitute $k=n-i$:

\begin{align*} \sum_{i=0}^n2i\binom{2n}{n-i}&=\sum_{k=0}^{n-1}2(n-k)\binom{2n}k\\ &=2n\sum_{k=0}^{n-1}\binom{2n}k-2\sum_{k=0}^{n-1}k\binom{2n}k\\ &=2n\sum_{k=0}^{n-1}\binom{2n}k-4n\sum_{k=1}^{n-1}\binom{2n-1}{k-1}\\ &=2n\left(\sum_{k=0}^{n-1}\binom{2n}k-2\sum_{k=0}^{n-2}\binom{2n-1}k\right)\\ &=2n\left(\sum_{k=0}^{n-1}\binom{2n}k-\sum_{k=0}^{n-2}\left(\binom{2n-1}k+\binom{2n-1}{2n-1-k}\right)\right)\\ &=2n\left(\sum_{k=0}^{n-1}\binom{2n}k-\sum_{k=0}^{n-2}\binom{2n-1}k-\sum_{k=n+1}^{2n-1}\binom{2n-1}k\right)\\ &=2n\left(\sum_{k=0}^{n-1}\binom{2n}k-\left(2^{2n-1}-\binom{2n-1}{n-1}-\binom{2n-1}n\right)\right)\\ &=2n\left(\sum_{k=0}^{n-1}\binom{2n}k-2^{2n-1}+\binom{2n}n\right)\\ &=n\left(2\sum_{k=0}^{n-1}\binom{2n}k-2^{2n}+2\binom{2n}n\right)\\ &=n\left(2^{2n}-\binom{2n}n-2^{2n}+2\binom{2n}n\right)\\ &=n\binom{2n}n\;. \end{align*}

I still haven’t found a combinatorial argument, though.

\begin{align} \sum_{i=1}^{n}{2i\binom{2n}{n-i}} & =\sum_{i=1}^{n}{(n+i)\binom{2n}{n-i}}-\sum_{i=1}^{n-1}{(n-i)\binom{2n}{n-i}} \\ & =\sum_{i=1}^{n}{2n\binom{2n-1}{n-i}}-\sum_{i=1}^{n-1}{2n\binom{2n-1}{n-i-1}} \\ & =\sum_{i=0}^{n-1}{2n\binom{2n-1}{i}}-\sum_{i=0}^{n-2}{2n\binom{2n-1}{i}} \\ & =2n\binom{2n-1}{n-1} \\ & =n \binom{2n}{n} \end{align}